2018
DOI: 10.1155/2018/9502902
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Study on Site of Action of Sinapine Thiocyanate following Acupoint Herbal Patching

Abstract: Objective To investigate the site of action of sinapine thiocyanate (ST), following acupoint herbal patching (AHP). Methods Twenty Wistar rats were randomized into five groups (groups A, B, C, D, and E), and all groups received the same AHP in vivo. Skin samples were excised at 2 h, 4 h, 6 h, 10 h, and 26 h after AHP administration from group A to group E separately and the concentrations of ST in the skin were determined using a liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) method. A ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…26 Sinapine thiocyanate has a variety of biological activities, including anti-oxidant, anti-inflammatory, anti-radiation, anti-aging, anti-hypertensive, and anti-androgen activity, while also inhibiting angiogenesis. [27][28][29][30] It is reported that ST could also reduce cholesterol and low-density lipoprotein (LDL), significantly improve hypertension symptoms, prevent thrombosis, and attenuate thrombosis caused by inflammatory injury of vascular endothelial cells (VECs). 31 Sinapine thiocyanate improved vascular endothelial injury in hypertensive rats by inhibiting the activation of NLRP3 and the expression of related inflammatory factors (IL-1β and IL-18), and also alleviated human umbilical vein endothelial cells (HUVEC) injury induced by the administration of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…26 Sinapine thiocyanate has a variety of biological activities, including anti-oxidant, anti-inflammatory, anti-radiation, anti-aging, anti-hypertensive, and anti-androgen activity, while also inhibiting angiogenesis. [27][28][29][30] It is reported that ST could also reduce cholesterol and low-density lipoprotein (LDL), significantly improve hypertension symptoms, prevent thrombosis, and attenuate thrombosis caused by inflammatory injury of vascular endothelial cells (VECs). 31 Sinapine thiocyanate improved vascular endothelial injury in hypertensive rats by inhibiting the activation of NLRP3 and the expression of related inflammatory factors (IL-1β and IL-18), and also alleviated human umbilical vein endothelial cells (HUVEC) injury induced by the administration of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Therefore, AAT with this formula may contribute to the prevention of inflammatory and metabolic diseases. [20] Additionally, Cortex Cinnamomi and Flos Caryophylli are often applied to alleviate painful chronic diseases. [21,22] Correspondingly, the main acupuncture points used in combination include the Bladder meridian (BL), Ren meridian, and Du meridian according to clinical syndrome differentiation.…”
Section: Introductionmentioning
confidence: 99%